Adhesion of a self-etching adhesive to caries-affected dentin treated with different methods for caries removal: a preliminary study - Matos, Adriana Bona; de Azevedo, Cynthia Soares; Trevelin, Livia Tosi; Aranha, Ana Cecília Correa (Brazilian Dental Science, 2016)
Objective: The aim of this study was to evaluate the adhesion of a self-etching system to caries-affected dentin (CAD) and sound dentin (SD) after different caries removal techniques by using microtensile bond strength test (?TBS). Materials and Methods: Twenty-four extracted human molars with coronal carious lesions were used. The samples were randomly divided into 5 groups, according to caries removal method: G1 - negative control (no removal); G2 abrasive disc; G3 – slow speed steel bur; G4 - Nd:YAG laser (energy density 21.2J/cm2); G5 - Er:YAG laser (energy density 80.24J/cm2). SD and CAD/ infected dentin substrates were tested. Self-etch system (Clearfil SE Bond) was applied and resin crowns were built up. Results: One-way ANOVA showed statistically significant difference between experimental groups (p<0.001), with significantly lower results for infected dentin (G1), when compared to all other experimental groups. A statistically significant higher bond strength value was observed for SD irradiated with Er:YAG laser when compared to CAD. For bur and Nd:YAG laser specimens, SD and CAD showed the same bonding performance. Conclusion: infected dentin is not an adequate substrate for bonding; Nd:YAG laser and steel burs showed the same bonding performance for both SD and CAD; while both dentins, when irradiated by Er:YAG laser, did not adequately interact with self-etching system resulting in poor adhesion. Keywords: Er:YAG laser; Nd:YAG laser; Infected dentin; Dentin.